2005
DOI: 10.1063/1.1844751
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ga+ irradiation on magnetic and magnetotransport properties in (Ga,Mn)As epilayers

Abstract: We report on the magnetic and magnetotransport properties of ferromagnetic semiconductor (Ga,Mn)As modified by Ga + ion irradiation using focused ion beam. A marked reduction in the conductivity and the Curie temperature is induced after the irradiation. Furthermore, an enhanced negative magnetoresistance (MR) and a change in the magnetization reversal process are also demonstrated at 4 K. Raman scattering spectra indicate a decrease in the concentration of hole carriers after the irradiation, and a possible o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…The introduction of additional charged centers after irradiation, as discussed above, can lead to a more inhomogeneous spatial distribution of regions with the Mn impurity band ("metallic" regions) that can modify the character of the magnetic anisotropy. The H C increase after ion irradiation was observed earlier for (Ga,Mn)As, note that it was accompanied by T C decrease [6,7].…”
Section: Magnetic Propertiessupporting
confidence: 59%
“…The introduction of additional charged centers after irradiation, as discussed above, can lead to a more inhomogeneous spatial distribution of regions with the Mn impurity band ("metallic" regions) that can modify the character of the magnetic anisotropy. The H C increase after ion irradiation was observed earlier for (Ga,Mn)As, note that it was accompanied by T C decrease [6,7].…”
Section: Magnetic Propertiessupporting
confidence: 59%
“…A third path is the implantation of heavy ions in the GaMnAs sample. Beams of Ga + of 30 keV have been used to introduce deep trap levels in the epilayer [11]. In the two latter methods additional material is incorporated in the GaMnAs sample.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Being motivated by the prospect of controlling the carrier concentration in (Ga,Mn)As with this approach, we have recently reported a preliminary experiment on the influence of Ga + ion irradiation on the ferromagnetic properties of (Ga,Mn)As using a focused ion beam (FIB) technique. [9] However, a systematic variation in the ferromagnetic features of (Ga,Mn)As was not obtained, although a sure sign that Ga + ion irradiation altered the hole carrier concentration and the corresponding magnetic properties was detected.…”
mentioning
confidence: 94%
“…In our recent studies, [10,14] it has been found that the in-plane magnetic anisotropy of (Ga,Mn)As/GaAs(001), which is composed of both 100 cubic magnetocrystalline anisotropy and [110] uniaxial anisotropy, [13,14,15] strongly depends on hole concentration, and that the contribution of [110] uniaxial anisotropy is enhanced with increasing hole concentration. [9,14] Thus, it is likely that 0.1 irradiated samples, which show a small contribution of [110] uniaxial anisotropy, have a lower hole concentration than noniraddiated samples. [9,14] To obtain clearer information about the mechanism of the change in the transport properties and the magnetic anisotropy shown in Figs.…”
mentioning
confidence: 99%
See 1 more Smart Citation